2014
DOI: 10.1007/s11552-014-9656-4
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Scalpel Technique for Minimally Invasive Surgery: Percutaneously Looped Thread Transection of the Transverse Carpal Ligament

Abstract: PurposeThis study aims to develop an alternate technique for improving the surgical procedure of carpal tunnel release.MethodThe transverse carpal ligament is transected by utilizing a piece of thread looped percutaneously under the visualization of ultrasound. The procedure, the thread carpal tunnel release (TCTR), was performed on 34 hands of 20 patients. Self-administrated Levine-Katz questionnaire was used for assessing the symptom severity and functional status of the outcomes.ResultsTCTR was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
106
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(110 citation statements)
references
References 26 publications
(34 reference statements)
4
106
0
Order By: Relevance
“…Although innovative, USCTR is not a new concept. To date, more than 600 clinical cases of USCTR have been reported in the peer-reviewed literature with no reported neurovascular complications and a clinical success rate commensurate with that reported for open and ECTR [4][5][6][7][8][9][10][11]. Furthermore, a recently published level 1 prospective randomized controlled trial comparing miniopen CTR (n ¼ 41) with USCTR (n ¼ 41) using a hook knife reported a 5-time faster functional recovery and pain medication discontinuation with USCTR [4].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although innovative, USCTR is not a new concept. To date, more than 600 clinical cases of USCTR have been reported in the peer-reviewed literature with no reported neurovascular complications and a clinical success rate commensurate with that reported for open and ECTR [4][5][6][7][8][9][10][11]. Furthermore, a recently published level 1 prospective randomized controlled trial comparing miniopen CTR (n ¼ 41) with USCTR (n ¼ 41) using a hook knife reported a 5-time faster functional recovery and pain medication discontinuation with USCTR [4].…”
Section: Discussionmentioning
confidence: 86%
“…Although initially performed via a large (3-5 cm) palmar incision, CTR techniques have continually evolved to reduce recovery times and postoperative pain as well as improve cosmesis and clinical outcomes [2,3]. More recently, multiple authors have reported excellent results after ultrasound-guided carpal tunnel release (USCTR) using a variety of techniques, and one prospective randomized trial reported faster recovery after USCTR compared with traditional mini-open CTR [4][5][6][7][8][9][10][11]. However, there is a paucity of data with respect to changes in the median nerve after USCTR [12][13][14].…”
mentioning
confidence: 99%
“…We acknowledge that some will have safety concerns with nontraditional surgeons performing this procedure. However, a simple review of the literature reveals that more than 600 ultrasound-guided carpal tunnel releases have been performed by a variety of specialists with no reports of injuries [5][6][7]17]. This iatrogenic injury rate is lower than what is reported as it relates to open (0.49%) and endoscopic (0.19%) releases [4].…”
Section: Discussionmentioning
confidence: 93%
“…Surgical releases include either open or endoscopic techniques, the latter being more controversial given its steeper learning curve [4]. Since 1997, more than 621 ultrasound-guided carpal tunnel releases (UGCTRs) using a variety of techniques have been published, with no reports of iatrogenic injuries [5][6][7]. This case demonstrates bilateral UGCTR using dynamic expansion of the transverse safe zone in a forearm crutch ambulator with postpolio syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] To reduce the long surgical wait times and ensure faster access to high-quality health care, innovative officebased TCL release procedures using ultrasound (US) guidance have gathered attention. Novel surgical tools like angle knife, 10 needle tips, 11,12 saw knife, 13 thread wire, 14 and hook knife [15][16][17] have been tested to resect the TCL under real-time ultrasonography with variable success in cadaveric studies. Only the hook knife CTR procedure has shown promising results in a clinical trial.…”
Section: Introductionmentioning
confidence: 99%